Adverse childhood experiences and transcriptional response in school-age children. (28th August 2022) - Marie-Mitchell, A.; Cole, S.W.
Abstract: This study evaluated whether children with higher adverse childhood experiences (ACE) scores had alterations in immune cell gene expression profiles. RNA sequencing was conducted on dried blood spot samples from 37 generally healthy English-speaking children (age 5–11) who were recruited from well-child visits at a university-affiliated pediatric practice. The Whole Child Assessment was used to assess ACE exposure. Primary analyses examined an a priori-specified composite of 19 pro-inflammatory gene transcripts. Secondary analyses examined a 34-gene composite assessing Type I interferon response, and used Transcript Origin Analyses to identify cellular mechanisms. After controlling for age, body mass index percentile, sex, race/ethnicity, current insurance status, and household smoking exposure, pro-inflammatory gene expression was elevated by 0.094 log2 RNA expression units with each Child-ACE total score point ( p = .019). Type I interferon gene expression was similarly upregulated (0.103; p = .008). Transcript origin analyses implicated CD8+ T cell as the primary sources of gene transcripts upregulated, and nonclassical (CD16+) monocytes as sources of downregulated transcripts. These preliminary analyses suggest that parent-reported ACE exposures are associated with increased expression of both inflammatory and interferon gene transcripts in children's circulating blood cells.